Exploratory Literature Meta‐Analysis to Characterize the Relationship Between Early and Longer Term Body Weight Loss for Antiobesity Compounds. (7th July 2016) - Plock, Nele; Bax, Leon; Lee, Douglas; DeManno, Deborah; Lahu, Gezim; Pfister, Marc
Abstract: The presented analysis was performed to characterize the relationship between treatment‐related early (week 4) and longer term (3–6 months) weight loss to understand the potential utility of 4‐week proof‐of‐mechanism studies in the early decision‐making process during clinical development of new antiobesity compounds. A regression‐based meta‐analysis was performed leveraging publically available clinical outcomes data to (1) characterize the within‐trial relationship between treatment‐related early and longer term body weight loss and (2) identify and quantify key covariate effects on this relationship. Data from 89 randomized clinical trials with 209 treatment arms, representing observations from 54 461 patients and 9 treatments, were available for the meta‐analysis. Results indicated that (1) there is a correlation between treatment‐related early and longer term body weight loss ( r > 0.9), (2) baseline body weight influences the relationship between early and longer term weight loss, whereas comorbidity such as type 2 diabetes mellitus, class of drugs including GLP‐1 analogues and the antiobesity compounds lorcaserin or phentermine/topiramate showed no significant effects on this relationship. The model was externally evaluated with data from the investigational compound beloranib, for which longer term weight loss could be successfully predicted based on early response data. Based on these results, the identified strong relationship between treatment‐related early and longer term weight loss appears to be independent of mechanism of action. Thus, findings from this analysis can optimize design of clinical studies and facilitate development of new anti‐obesity compounds.